Analytical study of important features of social life in the Ottoman Caliphate - Shagufta Naveed; Riyasat Ali (jihat-ul-islam, 2021)
Islam is a complete code of life that guides all spheres of life, be it cultural, military, political, social or economic. It encourages people to live together. In order to realize this goal, the Prophet of Islam laid a solid basis for the establishment of Islamic society . He presented the best example to the Ummah which is a guide for every individual of human society. It created an Islamic, reformist, benevolent, compassionate, and humanitarian society. Due to this, unforgettable changes took place in the lives of the Companions. After that, Islamic civilization expanded. In Muslim History, Muslims set the best examples in food, clothing, manners, ethics, linguistics, customs, hospitality, honesty and integrity. During the Ottoman Caliphate, Muslims continued this cultural tradition. Social life was multifaceted during this period. Parents were respected. Simplicity was preferred. Great care was taken for cleanliness. Hospitality was given with great enthusiasm. All forms of alcohol were avoided. Theft and robbery were very rare. Women were looked upon with respect. Hanafi jurisprudence was followed religiously. In this context, it can be said that social life was ideal in the Ottoman Caliphate. They were the pioneer of the best Islamic civilization. They have played an outstanding and unique role in the development of Islamic civilization. There is a need to describe the features and characteristics of the social life of this period in the light of these historical facts so as to pave the way for its use in the present period. This topic of research has been chosen to meet this intellectual and cultural need.